Appearance and Precipitation Characteristics of High-Latitude Pulsating Aurora - Partamies, Noora; Tesema, Fasil; Bland, Emma (Frontiers in Astronomy and Space Sciences, 2022)
Characteristics of pulsating aurora (PsA) at the equatorward part of the auroral oval have been well described in the literature by previous studies. We extend our knowledge on high-latitude PsA observations by analysing 68 PsA events from the optical observatory on Svalbard, at 75 degrees magnetic latitude. We found that the pulsating emission structures are particularly large and transient, they do not experience drift motion, or their drift motion cannot be traced. Our results show that the high-latitude PsA events relate to lower geomagnetic activity and weaker solar wind driving than the lower latitude PsA. The high-latitude PsA events also occur less frequently, which is in agreement with their association to lower-than-average geomagnetic activity. We further show that the ionospheric electron density values during high-latitude PsA events are low compared to the lower latitude PsA. This, together with the non-traceable nature of the pulsating emission structures, suggests that these events are strongly dominated by a sub-type called Amorphous Pulsating Aurora (APA). We therefore conclude that, unlike the lower latitude PsA events, the high-latitude PsA events are not likely to cause direct changes in the chemical composition of the mesosphere.